2014
DOI: 10.1177/0956462414534833
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy outperformed in a comparison of five methods for detecting Trichomonas vaginalis in symptomatic women

Abstract: In the UK, despite its low sensitivity, wet mount microscopy is often the only method of detecting Trichomonas vaginalis infection. A study was conducted in symptomatic women to compare the performance of five methods for detecting T. vaginalis: an in-house polymerase chain reaction (PCR); Aptima T. vaginalis kit; OSOM ®Trichomonas Rapid Test; culture and microscopy. Symptomatic women underwent routine testing; microscopy and further swabs were taken for molecular testing, OSOM and culture. A true positive was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…In this study, as in other evaluations of trichomonas culture sensitivity (18,24), there was a slight benefit to performing NAATs (Table 4); however, this is based on 5 days of reading the InPouch and is, thus, slow, labor-intensive, and requires highly skilled microscopists. Further, the lack of a standard that includes NAATs is known to inflate the sensitivity estimates of culture, and thus the marginal difference in sensitivity would likely expand to a larger difference if a composite infection standard (CIS) based on multiple NAATs had been possible during this trial.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, as in other evaluations of trichomonas culture sensitivity (18,24), there was a slight benefit to performing NAATs (Table 4); however, this is based on 5 days of reading the InPouch and is, thus, slow, labor-intensive, and requires highly skilled microscopists. Further, the lack of a standard that includes NAATs is known to inflate the sensitivity estimates of culture, and thus the marginal difference in sensitivity would likely expand to a larger difference if a composite infection standard (CIS) based on multiple NAATs had been possible during this trial.…”
Section: Discussionmentioning
confidence: 89%
“…Several investigations revealed successfully amplified DNA specimens extracted from cytological Pap-stained smears. Most of them demonstrated that the PCR method is a useful complementary technique for Pap-stained cellular samples [20,21]. In contrast, Chen et al [22] reported that PCR amplification from archival Pap-stained smears was unsuccessful, and they stated that the PCR was possibly inhibited by hematoxylin and aluminum sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that a number of cases were misdiagnosed because of the presence of Trichomonas -like atypical cervical cells [15]. Nathan et al [21] showed the number of trichomoniasis cases that are routinely missed even in symptomatic women if microscopy is the only diagnostic method available. Hence, our PCR method could be considered as a valuable alternative technique to rule out etiological agents of STI other than T. vaginalis in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, the use of this test has improved case finding significantly compared to the number of cases found by only microscopy. In studies comparing the OSOM assay with nucleic acid amplification tests (NAATs), the POC test performed quite well, with sensitivity similar to that of NAATs (Ͼ80% compared to NAATs at Ͼ90%) (24,25). The only drawback to this test is that it can only be used for women and cannot be bundled with POC chlamydia/gonorrhea screening.…”
Section: Diagnosticsmentioning
confidence: 99%
“…While motile trichomonads are very distinctive if observed microscopically, the organism load required in order to capture sufficient organisms for visualization is unknown. Comparison with newer diagnostic assays suggests that wet preparation microscopy is only 40 to 60% sensitive, even among symptomatic women (24). However, observation of motile trichomonads is highly specific and thus is very useful for determining a course of treatment.…”
Section: Diagnosticsmentioning
confidence: 99%